PEMBERDAYAAN MASYARAKAT BERBASIS POTENSI LOKAL DALAM PROGRAM “MERINTIS KAMPUNG LITERASI MEDIA DI DESA WARUNGASEM KECAMATAN WARUNGASEM KABUPATEN BATANG, JAWA TENGAH” - Ahmad Hidayatullah; Muhandis Azzuhri; Teddy Dyatmika (Swadaya: Indonesian Journal of Community Empowerment, 2019)
Technological progress is a necessity that must be faced by all parties, including the emergence of positive and negative impacts that exist. Furthermore, this inability to cope with change and progress will bring about the consequences of negative impacts, including those related to media development. And this must be overcome, through various efforts, one of which is the media literacy movement. Using qualitative research methods that are done by working with data, organizing data, sorting it out, searching and finding patterns, finding what is important to report, this article tries to uncover how the implementation of Local Potential-based Community Empowerment in the "Pioneering Media Literacy Village" Program in Warungasem Village Warungasem District Batang Regency ". The results of this study are that media literacy-based community empowerment programs are carried out by synergizing four activity clusters, namely Journalistic and Web Clusters, Photography and Videography Clusters, E-Commerce Clusters and Design and Environment Clusters. The four clusters are synergized to realize Warungasem as Media Literacy Village. Keywords: media literacy village, community empowerment, local potential-based.